2019
DOI: 10.1029/2019jc015267
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Pathways of the South Atlantic: Revisiting the Cold and Warm Water Routes Using Observational Data

Abstract: The relative contributions of the Atlantic Meridional Overturning Circulation upper limb source waters in the South Atlantic (SA) remain largely unresolved. We contribute to a resolution by using observational data to explore water mass pathways feeding into the Benguela Current, considered a major component of the Atlantic Meridional Overturning Circulation upper limb in the SA. We focus on the pathways from the Pacific Ocean via the Drake Passage (traditionally termed the “cold” water route) and the Indian O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
(149 reference statements)
0
16
1
Order By: Relevance
“…Richardson () found similar leakage percentages: 23% for the ALACE floats, 18% for the RAFOS floats, and 33% for the GDP drifters. Our results and his are very different from those of Drouin and Lozier () who found that less than 10% of drifters leaked. The inconsistency comes mainly in their denominator, which includes drifters outside the southwestward flow of the Agulhas Current which are not heading into the retroflection, as well as those that remain in the retroflection region, which we discount on the basis that we cannot be sure whether they eventually leak or not.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Richardson () found similar leakage percentages: 23% for the ALACE floats, 18% for the RAFOS floats, and 33% for the GDP drifters. Our results and his are very different from those of Drouin and Lozier () who found that less than 10% of drifters leaked. The inconsistency comes mainly in their denominator, which includes drifters outside the southwestward flow of the Agulhas Current which are not heading into the retroflection, as well as those that remain in the retroflection region, which we discount on the basis that we cannot be sure whether they eventually leak or not.…”
Section: Resultscontrasting
confidence: 99%
“…We have found that retaining these resident drifters in simulations makes results sensitive to the lifetime of the particles (Cheng et al, ). Drouin and Lozier () also find that the drifter leakage percentage is very sensitive to the latitude used to define the Agulhas Current crossing with a decrease in leakage as the latitude is moved upstream. Taking only those drifters that pass through 32°S, however, we find nearly the same percentage of undrogued (12/36, 33%) and drogued drifters (8/25, 32%) that leak.…”
Section: Resultsmentioning
confidence: 96%
“…Natural remanent magnetization (NRM) was measured and stepwise demagnetized with a superconducting 2G Enterprises 755 SRM long-core magnetometer. Demagnetization was accomplished in 10 steps at AF peak levels of 5,10,15,20,30,40,50,65,80, and 100 mT. NRM results were analysed with principle component analysis 63 to determine direction of the characteristic remanent magnetization (ChRM).…”
Section: Methodsmentioning
confidence: 99%
“…Core PS67/197-1 in the Scotia Sea is sensitive to changes in winter sea ice extent 17 . Light blue arrows show the Antarctic Circumpolar Current (ACC), the Cape Horn Current (CHC) 19 and Malvinas Current (MC) 20 , while dark green-blue arrows are Weddell Sea Bottom Water (WSBW, thick) and Weddell Sea Deep Water (WSDW, thin) flows 21 . White dotted line is average modern winter sea ice edge 22 .…”
mentioning
confidence: 99%
“…For the description given hereafter, the reader who is not familiar with South Atlantic large-scale circulations and its ocean currents is referred to Figure 3 from , to aid visual interpretation. (R ühs et al, 2019;Drouin and Lozier, 2019;.…”
Section: Characterization Of the General Mean Circulation Fieldmentioning
confidence: 99%